Hospices in partnership? Public health, end of life, and the responsibility of hospices. (February 2016) - Hartley, Nigel
Abstract : Public health approaches to palliative care must appreciate that health professionals are part of communities, and the importance of partnerships should not be ignored – despite the inherent challenges. The true partners in a public health approach towards the end of life are of course, dying people, their families and friends, and members of the communities within which they are living and dying. However, we ignore important partnerships with nurses, doctors, and other healthcare professionals at our peril. This paper situates hospices within the broader community and uses vignette's to highlight approaches to community engagement and the challenges of partnership.